DECODING DIGITAL YOUTH: COMMUNICATION TRENDS IN THE INTERNET ERA - Kochunts, Karine (Armenian Folia Anglistika, 2024)
The article focuses on increasing developments in the structure of the language of online communication. It is already common knowledge that online communication or otherwise, multimedia communication has set quite specific language rules, especially in the ways of encoding and, consequently, decoding messages. The so-called “new normal” has gradually crept into reality, even if virtual, unnoticed, and seems to have stayed. The “new normal” does not remain the same and changes with time and the new requirements of the users. The ever-growing striving of people to make things work faster has not left the sphere of human communication untouched, particularly, informal online communication. Thus, most of the changes in the means of encoding a message primarily aim at brevity and efficiency. It is noteworthy that changes are mainly implemented by young users of online space. It is usually they who set new trends in the ways and means of coding meaning in the text, often posing challenges and risks in balancing personal and professional boundaries.